2018
DOI: 10.4132/jptm.2018.09.13
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Adipophilin Is Frequently Found in Solid Subtype Adenocarcinoma and Is Associated with Adverse Outcomes in Lung Adenocarcinoma

Abstract: BackgroundThe up-regulation of the lipogenic pathway has been reported in many types of malignant tumors. However, its pathogenic role or clinical significance is not fully understood. The objective of this study was to examine the expression levels of adipophilin and related hypoxic signaling proteins and to determine their prognostic impacts and associations with the pathologic characteristics of lung adenocarcinoma.MethodsExpression levels of adipophilin, heat shock protein 27 (HSP27), carbonic anhydrase IX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The accumulation of intracellular lipid droplets is a usual observation in ischemic tissues, such as organ infarction [7]. In cancer, hypoxic signaling usually is activated by ischemia and is related to an aggressive phenotype [7,31]. It is suggested that the coordination of the metabolic deregulation and hypoxic signaling contributed to the biological aggressiveness of lung adenocarcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of intracellular lipid droplets is a usual observation in ischemic tissues, such as organ infarction [7]. In cancer, hypoxic signaling usually is activated by ischemia and is related to an aggressive phenotype [7,31]. It is suggested that the coordination of the metabolic deregulation and hypoxic signaling contributed to the biological aggressiveness of lung adenocarcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, hypoxic signaling usually is activated by ischemia and is related to an aggressive phenotype [7,31]. It is suggested that the coordination of the metabolic deregulation and hypoxic signaling contributed to the biological aggressiveness of lung adenocarcinoma [31]. To verify these three hypotheses, further studies of the functional role of ADP in SDC is required.…”
Section: Discussionmentioning
confidence: 99%
“…Adipophilin has emerged as a prognostic biomarker in different cancer types, including colorectal, lung, breast, ovarian, clear cell renal cell carcinoma, and cutaneous malignant melanoma [40][41][42][43][44][45]. UM prognostication for predicting metastatic risk and patient management, involves the combination of clinical, morphological, Adipophilin as a metabolic biomarker for uveal melanoma 213…”
Section: Discussionmentioning
confidence: 99%
“…The included studies used quantitative real-time-polymerase chain reaction or immunohistochemistry to detect the expression level of PLIN2, and all patients were divided into high or low PLIN2 expression groups by cutoff value. In the included studies, there were 10 different malignancies: breast cancer, [34][35][36][37][38] ccRCC, 18,39,40 cutaneous malignant melanoma, 41 HB, 19 hepatocellular carcinoma, 42 highgrade serous ovarian carcinoma, 43 lung adenocarcinomas, 44,45 oral squamous cell carcinoma, 46 pancreatic ductal adenocarcinoma, 47 and salivary duct carcinoma. 48 The result of analysis of survival data from the included studies were obtained following patients for 40-300 months.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%